Comprehensive Genomic Profiling of Esthesioneuroblastoma Reveals Additional Treatment Options. (11th May 2017) - Gay, Laurie M.; Kim, Sungeun; Fedorchak, Kyle; Kundranda, Madappa; Odia, Yazmin; Nangia, Chaitali; Battiste, James; Colon‐Otero, Gerardo; Powell, Steven; Russell, Jeffery; Elvin, Julia A.; Vergilio, Jo‐Anne; et al.
Abstract : Background: Esthesioneuroblastoma (ENB), also known as olfactory neuroblastoma, is a rare malignant neoplasm of the olfactory mucosa. Despite surgical resection combined with radiotherapy and adjuvant chemotherapy, ENB often relapses with rapid progression. Current multimodality, nontargeted therapy for relapsed ENB is of limited clinical benefit. Materials and Methods: We queried whether comprehensive genomic profiling (CGP) of relapsed or refractory ENB can uncover genomic alterations (GA) that could identify potential targeted therapies for these patients. CGP was performed on formalin‐fixed, paraffin‐embedded sections from 41 consecutive clinical cases of ENBs using a hybrid‐capture, adaptor ligation based next‐generation sequencing assay to a mean coverage depth of 593X. The results were analyzed for base substitutions, insertions and deletions, select rearrangements, and copy number changes (amplifications and homozygous deletions). Results: Clinically relevant GA (CRGA) were defined as GA linked to drugs on the market or under evaluation in clinical trials. A total of 28 ENBs harbored GA, with a mean of 1.5 GA per sample. Approximately half of the ENBs (21, 51%) featured at least one CRGA, with an average of 1 CRGA per sample. The most commonly altered gene was TP53 (17%), with GA in PIK3CA, NF1, CDKN2A, and CDKN2C occurring in 7% of samples. Conclusion: We report comprehensive genomic profiles for 41 ENB tumors. CGP revealed potential new therapeutic targets, including targetable GA in the mTOR, CDK and growth factor signaling pathways, highlighting the clinical value of genomic profiling in ENB. Abstract : Comprehensive genomic profiling (CGP) using next‐generation sequencing was performed on a series of 41 clinical esthesioneuroblastoma samples. This study provides a view into the genomic landscape of esthesioneuroblastoma and insight into the biological mechanisms underlying this tumor type.